The "Public" Wrong of Cartels and the Article 101 TFEU "Object Box". (September 2020) - MacCulloch, Angus
The criminalization of cartel behavior in the UK turned attention to the criminal wrong at the heart of cartels. An understanding of the true nature of the cartel problem can also be used to develop a better understanding of Art 101 TFEU. This article uses the literature on the wrongfulness of cartels to examine how cartel behavior has the "object" of restricting competition within the terms of Art 101 TFEU. It pays particular attention to cases at the periphery of cartel behavior. The literature focuses on the importance of free markets as public institutions. Cartels are perceived as being a species of "cheating" which deserves opprobrium as it goes against the legitimate expectations of market participants. A reexamination of the cartel periphery cases involving information exchange and cartel facilitation using this lens shows a novel understanding of how these cases fit within the Art 101 TFEU "object box."